Climate Inequality: Carbon Capture for Redistribution - Elisa Belfiori; Manuel Macera (CESifo GmbH, 2024)
We study optimal climate policy in a global economy where regions differ in wealth and climate vulnerability. Carbon emissions from production lead to output losses, and there is a technology for emissions absorption. We provide an aggregation result: the model with heterogeneity can be cast into a representative region economy with a different discount factor and damage function. This result offers a simple rule to account for inequality in the design of climate policy. We show that wealthier regions should bear more responsibility for carbon capture to cleanse the atmosphere, and that inequality per se does not entail a compromise on emissions reduction. It is only if regions must contribute uniformly to carbon capture that the optimal climate policy dictates higher global net emissions relative to the first best. An important insight is that carbon capture serves as a redistribution tool when direct lump-sum transfers across regions are unfeasible.
Keywords: Q54; D63; E60; H41; H21; 330; heterogeneous regions; negative emissions; inequality; carbon capture